2022
DOI: 10.5056/jnm20236
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blinded, Placebo-controlled Study to Evaluate the Efficacy and Safety of DA-9701 (Motilitone) in Patients With Constipation-type Irritable Bowel Syndrome and Functional Dyspepsia Overlap: A Pilot Study

Abstract: published online; they have not yet been assigned to a journal issue. When these articles are published in an issue, they will be removed. Online First articles are copy-edited, typeset and approved by the authors before publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder that causes chronic diarrhea or constipation, stomach bloating, and abdominal cramping by affecting the gastrointestinal motility and immunity ( Ford et al., 2018 ; Lee et al., 2022 ; Raskov et al., 2016 ). However, the mechanism of IBS-related pathophysiology remains poorly understood.…”
Section: Trp Nutrition In Diseases Preventionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder that causes chronic diarrhea or constipation, stomach bloating, and abdominal cramping by affecting the gastrointestinal motility and immunity ( Ford et al., 2018 ; Lee et al., 2022 ; Raskov et al., 2016 ). However, the mechanism of IBS-related pathophysiology remains poorly understood.…”
Section: Trp Nutrition In Diseases Preventionmentioning
confidence: 99%
“… 8 , 9 , 10 Therefore, β 3 ‐adrenergic receptor activation has been suggested as a potential novel target for treating pain and modulating gastrointestinal motility in patients with IBS. 11 , 12 Evidence for the therapeutic potential of β 3 ‐adrenergic receptor activation in the treatment of IBS has been shown in preclinical studies, including ex vivo data showing β 3 ‐adrenergic receptor agonist inhibition of cholinergic contractions in isolated human colon, which was fully reversed in the presence of a β 3 ‐adrenergic receptor antagonist. 10 A pilot clinical trial demonstrated improved IBS‐related pain among women with IBS receiving a β 3 ‐adrenergic receptor agonist.…”
Section: Introductionmentioning
confidence: 99%
“… 10 A pilot clinical trial demonstrated improved IBS‐related pain among women with IBS receiving a β 3 ‐adrenergic receptor agonist. 12 …”
Section: Introductionmentioning
confidence: 99%